2024
DOI: 10.1037/ort0000708
|View full text |Cite
|
Sign up to set email alerts
|

The power of knowledge: How mental health literacy can overcome barriers to seeking help.

Yin-Ju Lien,
Ling Chen,
Jiyan Cai
et al.

Abstract: Mental health literacy (MHL) predicts help-seeking attitudes. However, the relationship between components of MHL and help-seeking attitudes has not been thoroughly examined. This study aims to examine whether mental illness stigma, help-seeking efficacy, and maintenance of positive mental health mediated the relationship between recognition of mental disorders and help-seeking attitudes, using a meta-analytic structural equation modeling (MASEM) approach. A comprehensive literature search was conducted to gat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 133 publications
0
2
0
Order By: Relevance
“…The young adults from the current study also reported these barriers. Providing education, both to young adults and their communities, as well as to (mental) health care providers generally, can generally help fight stigma, embarrassment and challenges associated with recognizing mental illness (46). Additionally, providing self-help therapy programs to cope with suicidal thoughts can help meeting the needs of young adults, while taking into account their desire for self-reliance (47).…”
Section: Facilitating Seeking Help For Mental Health Carementioning
confidence: 99%
“…The young adults from the current study also reported these barriers. Providing education, both to young adults and their communities, as well as to (mental) health care providers generally, can generally help fight stigma, embarrassment and challenges associated with recognizing mental illness (46). Additionally, providing self-help therapy programs to cope with suicidal thoughts can help meeting the needs of young adults, while taking into account their desire for self-reliance (47).…”
Section: Facilitating Seeking Help For Mental Health Carementioning
confidence: 99%
“…The young adults from the current study also reported these barriers. Providing education, both to young adults and their communities, as well as to (mental) health care providers generally, can generally help fight stigma, embarrassment and challenges associated with recognizing mental illness (46). Additionally, providing self-help therapy programs to cope with suicidal thoughts can help meeting the needs of young adults, while taking into account their desire for self-reliance (47).…”
Section: Facilitating Seeking Help For Mental Health Carementioning
confidence: 99%